Stratigraphy, facies analysis and paleoenvironments of the Cañadón Asfalto Formation, Jurassic Cerro cóndor depocenter, Chubut province - Cabaleri, N. (2010)
The Cerro Cóndor depocenter represents the most complete stratigraphic sequence of the continental Jurassic of the Cañadón Asfalto basin and southern South America. It is situated in extraandean Patagonia, on both sides of the middle Chubut river valley. The sedimentation in this pull-apart basin begins early in the Middle Jurassic, accompanied by effusions of olivinic basalts. The prevailing lacustrine deposits are characterized by carbonatic and siliciclastic facies associations, interfingering with volcanic deposits grading from lavic in the base to predominantly pyroclastic towards the top. The facies evolution from north to south is described, embracing the sections of farm El Torito and the canyons of Los Loros, Las Chacritas, Carrizal, Asfalto and Lahuincó. The carbonatic facies/microfacies are represented by mudstones, wackestones, packstones, grainstones and microbialitic limestones, characteristic of littoral/marginal and palustrine environments. In the Cañadón Asfalto Formation are distinguished a lower member (Las Chacritas composed by limestones, shales, sandstones and conglomerates intercalated with olivinic basalts, and an upper member (Puesto Almada) composed by tuffs, tuffites, shales and sandstones. The first is bearing a palynologic assemblage of Bajocian-Bathonian age and the second dinosaurs of Tithonian age. The stratigraphic sections of both members of the formation are described and illustrated at their type localities cañadón Las Chacritas and farm El Torito and the paleoenvironments of the depocenter, from the Aalenian to the Tithonian are described and illustrated. The age of the Puesto Almada Member at its type locality was obtained by radiometric dating (K/Ar) of biotites from a thin layer of volcanic tuff (147.1 + 3.3 Ma, Tithonian) from the upper part of the unit.